Densification and mechanical properties of pulsed electric current sintered B4C with in situ synthesized Al3BC obtained by the molten-salt method. Issue 15 (December 2017) - Ren, Donglou; Deng, Qihuang; Wang, Ji; Li, Youbing; Li, Mian; Ran, Songlin; Du, Shiyu; Huang, Qing
Abstract: The in situ generated ternary compound Al3 BC shows good dispersion on the surfaces of B4 C particles (10 ± 0.6 μm), obtained using the molten-salt method rather than the ball-milling method, which can form a conductive network in the pulse electric current sintering process to improve the sinterability of B4 C. The sintering behaviour, microstructure and mechanical properties of compacts were investigated at different sintering temperatures and Al3 BC contents. The study found that the relative density, elastic modulus, Vickers hardness, and fracture toughness of samples reached as high as 100%, 495 GPa, 37.0 GPa, and 6.32 MPa m 1/2 at 1700 °C, respectively, when the content of Al3 BC was 18 wt.%. The crack propagation mode can provide an explanation for the higher toughness than that of pure B4 C (3.19 MPa m 0.5 ). Additionally, the good dispersion of Al3 BC in B4 C was found to change the fracture mode from the single transgranular mode to a mixture of intergranular and transgranular modes. The compositions of the compacts were almost pure B4 C.